Sistem Pendukung Keputusan Berbasis Web Dengan Metode Weighted Product Penyeleksian Kandidat Ketua Dan Wakil Ketua Himafortika - Irsyadunas, Irsyadunas; Hatta, Arif Rahman; Safitri, Dian; Karimah, Mutiara; Marisa, Ratna; Pramana, Yogi (Journal of Student Development Information System (JoSDIS), 2023)
The purpose of this study was to design a Decision Support System (SPK) for selecting the Chair and Deputy Chairmen of Himafortika using the Weighted Product (WP) Method. So far, the process of selecting the chairman and deputy chairman of Himafortika is still experiencing problems, where the selection system still uses the manual method. The results of the selection are then submitted to the selection team to assess the candidates who will be elected as candidates for chairman and deputy chairman of the Hima. This system is designed using the programming language PHP and MySQL as the database. This system can rank candidates by calculating feature weights. The alternative used in this study is based on the average active student requirements, GPA 3.00, semester students, past photos and LKMM-T certificates. The results of this study are a decision support system that is made to find out the best and worthy candidates to become candidates for chairman and deputy chairman of the Hima based on the results of an assessment of the requirements for the candidate for chairman and deputy chairman of the Hima. The admin can input data on the requirements for chairperson and deputy chairperson candidates for each factor, then the system will find a solution using the Weighted Product (WP) method. After the decision is obtained, the system will display the decision.